EFEKTIVITAS PENGGUNAAN METODE CERAMAH DAN DEMONSTRASI PADA PEMBELAJARAN SENI TARI DI KELAS VII A SMP PEMBANGUNAN LABORATORIUM UNP - Wilya Aryana Putri; Indrayuda Indrayuda; Susmiarti Susmiarti (FBS Universitas Negeri Padang, 2018)
AbstractThis study was aimed to know and describe the effectiveness of lecture and demonstration methods and the cause of ineffective both of them on dance art learning at class VII A SMP Pembangunan Laboratorium UNP. This study was qualitative with descriptive method. Instrument in this study was the researcher and it was also assisted by some tools such as stationery, camera and audio visual recording tool. Technique of data collection was done by using observation, interview, library research and documentation. Result of this study showed that both the lecture and demonstration methods on dance art learning at class VIIA SMP Pembangunan Laboratorium UNP were ineffective yet. It could be seen from the students score who had not more reached minimal compeleteness criteria (KKM). The problem was caused by teachers who did not develop study well with using lecture and demonstration methods, teachers did not apply those methods optimally so that it could be seen that unstructured implementation of steps of the lecture and demonstration methods. Teachers did it randomly which caused those methods were used at class VII A SMP Pembangunan Laboratorium UNP were ineffective (not effective). Keywords: The Effectiveness, Lecture and Demonstration methods, Dance Art Learning.